Does corruption boost economic growth in developing countries? - Bouteraa, Mohamed; Tir, Abdelhak; Achour, Sadok; Rimi, Okba; Tamma, Elhachemi (Asian Economic and Financial Review, 2024)
Many countries with emerging economies suffer from a high level of corruption that hampers their overall development. Despite the abundance of literature scrutinizing the intricate relationship between corruption and economic growth, the precise nature of this connection remains elusive. To address this, this study rigorously examines the link between corruption and economic growth across 129 developing countries, spanning the years 2003 to 2021. The methodology relies on Transparency International's Corruption Perceptions Index (CPI) to gauge the extent of corruption within these nations. Employing the Plate-Corrected Standard Error (PCSE) estimator, we seek to derive a more robust and reliable measure of the correlation between corruption and growth. The noteworthy revelation of this investigation is that higher levels of corruption surprisingly correlate with increased economic growth in developing countries, thereby supporting the intriguing "grease the wheels" hypothesis. These findings challenge conventional assumptions and prompt a re-evaluation of the perceived negative impact of corruption on economic development. Furthermore, our analysis uncovers additional factors influencing economic growth in developing nations. Notably, Foreign Direct Investment (FDI) and revenues from oil contribute positively to economic growth, while augmented military expenditures emerge as a suppressant. These nuanced insights shed light on the multifaceted dynamics shaping economic trajectories in developing countries and underscore the complexity of the interplay between corruption and key economic indicators.